2019
DOI: 10.2136/sssaj2018.06.0225
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crops and Corn Residue Removal: Impacts on Soil Hydraulic Properties and Their Relationships with Carbon

Abstract: Large-scale crop residue removal may negatively affect soil water dynamics. Integrating cover crop (CC) with crop residue management can be a strategy to offset potential adverse effects of residue removal. We studied: (i) the impact of corn (Zea mays L.) residue removal (56%) with and without the use of winter rye (Secale cereale L.) CC on soil hydraulic properties, (ii) whether CC would ameliorate residue removal effects on hydraulic properties, and (iii) relationships of hydraulic properties with soil organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
2
33
2
Order By: Relevance
“…The highest value (27%) of this parameter was recorded in NT with full retention of crop residue (NTR 100 ), while the lowest (~15%) values were observed under CT without residue application (CTR 0 ). The present results are in agreement with the findings of the others [70,98]. In the NT, soil layer of 0-10 cm had significantly higher available water content than that of 10-20 cm, whereas, in CT, the differences between two depths were not significant (Tables 5 and 6).…”
Section: Available Watersupporting
confidence: 93%
“…The highest value (27%) of this parameter was recorded in NT with full retention of crop residue (NTR 100 ), while the lowest (~15%) values were observed under CT without residue application (CTR 0 ). The present results are in agreement with the findings of the others [70,98]. In the NT, soil layer of 0-10 cm had significantly higher available water content than that of 10-20 cm, whereas, in CT, the differences between two depths were not significant (Tables 5 and 6).…”
Section: Available Watersupporting
confidence: 93%
“…For example, CCs may not change water infiltration until other properties, such as aggregate stability and porosity, improve. Indeed, soil pore‐size distribution, which directly affect water transmission characteristics, are slow to change, particularly under low rates of CC biomass production (Sindelar et al., 2019a). Potential factors influencing changes in water infiltration after CC adoption are discussed below.…”
Section: Do Cover Crops Enhance the Ability Of The Soil To Capture Anmentioning
confidence: 99%
“…A synthesis of global literature on the effects of CCs on soil compaction, aggregation, pore‐size distribution, saturated and unsaturated flow, water retention and available water, thermal processes, and others can be valuable to advance our understanding of CC management impacts on soil physical environment. Some individual studies on CCs reported that CC effects on soil physical properties can be variable depending on soil type, CC species, CC biomass production, tillage and cropping system, and climate (Blanco‐Canqui & Jasa;, 2019; Ruis et al., 2020; Sindelar, Blanco‐Canqui, Virginia, & Ferguson, 2019a, 2019b). Also, an increase in soil organic C (SOC) is often considered to improve soil physical properties, but such correlations across CC studies have not been widely discussed to better understand the mechanisms by which CCs can improve soil physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the general belief that cover crops (CCs) can improve soil properties and productivity, research data suggest that CC impacts on soil properties, particularly soil physical properties, are inconsistent. Recent studies from different regions reported that CCs can have variable effects on soil physical properties (Barker et al, 2018; Blanco‐Canqui et al, 2017; Dozier et al, 2017; Rorick and Kladivko, 2017; Sindelar et al, 2019). A review of published studies from temperate regions also concluded that CC effects on soil ecosystem services can be variable (Blanco‐Canqui et al, 2015).…”
mentioning
confidence: 99%